PERBEDAAN PENILAIAN PENGUNJUNG KELUARGA DAN NON-KELUARGA TERHADAP ATRIBUT WISATA DAERAH PERBUKITAN DI BANDAR LAMPUNG - Nurhanif, Muhammad Daffa; Hudoyo, Agus; Indriani, Yaktiworo (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
ABSTRACT This research aims to analyse the differences between family visitors and non-family visitors in assessing the importance of the attributes of hilly area tourism and to rank the importance of these attributes. Additionally, it seeks to analyse which performance-related qualities should be preserved and which require improvement. 35 family visitors and 35 non-family visitors were interviewed for 16 qualities as part of this study's survey methodology. Probability sampling was used to choose the sample. Importance Performance Analysis (IPA) and the Mann-Whitney test were used for data analysis. When evaluating the value of traits, family visitors and non-family visitors differ in six ways, according to the results of the Mann-Whitney test. Meanwhile, the five attributes with the highest importance rankings in the assessment based on family visitors were comfort while traveling, scenery, air quality, safety while traveling, and food courts. In contrast, the assessment of non-family visitors highlights the five attributes with the highest importance rankings as air quality, scenery, comfort while traveling, tranquillity while traveling, and price. Furthermore, the combined results of the IPA analysis on family visitors and non-family visitors concluded that there were five attributes that need to be improved and nine attributes that need to maintain their performance. Key words: Attributes, Family and Non-family, Importance and Performance, and Importance Performance Analysis (IPA).